2018
DOI: 10.1002/bab.1654
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a camelid single‐domain antibody directed to human CD22 biomarker

Abstract: CD22 is a B-cell-specific trans-membrane glycoprotein, which is found on the surface of the most B cells and modulates their function, survival, and apoptosis. Recently, targeting this cell surface biomarker in B-cell malignancies and disorders has attracted a lot of attention. The variable domain of camelid single-chain antibodies (VHH, nanobody) is a form of antibodies with novel properties including small size (15-17 kDa), thermal and chemical stability, high affinity and homology to human antibody sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…4446 An immuno-conjugate that integrates urease enzyme with the ability of pH alkalisation in TME is currently undergoing clinical trials in lung cancer but has not been tested in prostate cancer. 47,48 Despite the efficacy of those modalities evident in preclinical studies, no studies had been conducted to investigate their impact on TME. Among the many future therapeutic applications of the current study is to test whether pH-sensitive macrophage-specific immuno-conjugates or nano-systems that specifically target acidic areas rich in macrophages can reduce immunosuppression and increase T cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…4446 An immuno-conjugate that integrates urease enzyme with the ability of pH alkalisation in TME is currently undergoing clinical trials in lung cancer but has not been tested in prostate cancer. 47,48 Despite the efficacy of those modalities evident in preclinical studies, no studies had been conducted to investigate their impact on TME. Among the many future therapeutic applications of the current study is to test whether pH-sensitive macrophage-specific immuno-conjugates or nano-systems that specifically target acidic areas rich in macrophages can reduce immunosuppression and increase T cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study challenged here different modes of bacterial production and showed how these can impair VHH key attributes such as yield, homogeneity, structure and function. It is somewhat surprising that an area of such great potential be too often poorly characterized in terms of biophysical properties, despite beautiful biological data obtained with those objects [84][85][86][87][88][89]. Therefore, we embarked in a multi-stage characterization process during which model functional VHHs were thoroughly analyzed for their…”
Section: Discussionmentioning
confidence: 99%
“…Construction of a naive nanobodies phage-displayed library was described as Faraji (Faraji et al, 2018). In brief, total RNA was extracted using a total RNA isolation system (Thermo Fisher Scientific, Waltham, MA, USA) from llama peripheral blood lymphocytes.…”
Section: Naive Nanobodies Phage-displayed Library Constructionmentioning
confidence: 99%